PESERTA DIDIK DALAM PANDANGAN NATIVISME, EMPIRISME, DAN KONVERGENSI - Musdalifah Musdalifah (Universitas Islam Negeri Alauddin Makassar, 2018)
Abstract:To achieve the objectives of learning in the classroom many things are needed, because the process is a complex phenomenon. One of the influences is the educator's understanding of the existence of students. Educators must know the views of various streams of education about students. This paper focuseses on nativism, empiricism, and convergence in understanding students. The flow of nativism holds that the development of students is determined from birth. This stream believes that human development is determined by its defenders. Environmental factors have less influence on children's education and development. Therefore, the results of education are determined by birth-born talent. The flow of empiricism assumes that children born into the world are like white paper. White paper will have patterns and writing that are scratched by the environment. Educators as external factors play a very important role, because educators provide an educational environment for children, and children will receive education as experience. This experience will shape the behavior, attitudes, and character of the child based on the educational goals.